Indiscretion of an American wife - De Sica, Vittorio, 1901-1974; Jones, Jennifer, 1919-2009; Clift, Montgomery; Zavattini, Cesare, 1902-1989.; Produzioni De Sica S.A.; Cinetel Films ([Rome, Italy] : Produzioni De Sica S.A., 1953)
A married American woman has gotten involved with another man while visiting relatives in Rome. She decides that the time has come to break off the relationship, and she makes plans to return home to her husband. But she soon realizes that she is not at all sure about what she wants to do, and she continues to agonize over her decision. --
A Selznick release.
Based on the story: Terminal station / Cesare Zavattini.
Jennifer Jones, Montgomery Clift, Gino Cervi, Dick Beymer
Cinematographer, G.R. Aldo; editors, Eraldo Da Roma, Jean Barker; music, Alessandro Cicognini.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: Man-woman relationships -- Drama; Adultery -- Drama; Roma Termini (Rome, Italy) -- Drama; Italy -- Drama; Romance films; Internet videos; Streaming video